Non local means denoising in photoacoustic imaging. (19th April 2018) - Siregar, Syahril; Nagaoka, Ryo; Haq, Israr Ul; Saijo, Yoshifumi
Abstract: Photoacoustic (PA) imaging has the ability to visualize human organs with high spatial resolution and high contrast. Like digital images, PA images are contaminated with random noise due to some parameters. The band-pass filter does not effectively remove the noise because noise is randomly distributed in the bandwidth frequency. We present noise removal method in PA images by using non local means denoising (NLMD) method. The NLMD can be used if there are similarities or redundancies in the image. PA images contain of blood vessel which repeating on the small patch. The method was tested on PA images of carbon nanotubes in micropipe, in vivo mice brain and in vivo mice ear. We estimated the suggested input parameters of NLMD, so it can be automatically applied after scanning the image in PA imaging system. Our results declared that the NLMD enhanced the image quality of PA images.